Joint precoder and decoder design in downlink multi-user MIMO C-RAN with imperfect CSI - Lu, Jiacheng; Zhang, Jun; Yang, Shizhao; Cai, Shu; Ni, Yiyang (Physical communication, 2021)
Compared with traditional network structure, cloud-radio access network (C-RAN) can provide higher capacity with lower latency transmission performance. Meanwhile, more user equipment will require more radio remote heads (RRHs) in the same region. This paper studies the cancellation of interference from adjacent RRHs and maximization for sum-rate based on the limitation that imperfect channel state information is known at RRHs in a downlink multiple-input multiple-output C-RAN scenario, where line-of-sight and scattered components are both considered. We adopt the mutual information tight lower bound to substitute channel capacity designing criterion for the exact form of the latter is hard to obtain. Owing to the non-convexity of the problem based on lower bound designing criterion, we transform the problem into a convex form and give the optimal structure of precoding and decoding matrices by proving the equivalence between the minimum mean square error and the original objective function. Numerical results show that the proposed iterative algorithm effectively improves the transmission capacity and eliminates coherent interference between RRHs by jointly precoding and decoding.